Static balance of visually impaired paralympic goalball players - Bednarczuk, G.; Molik, B.; Morgulec-Adamowicz, N.; Kosmol, A.; Wiszomirska, I.; Rutkowska, I.; Perkowski, K. (International Journal of Sports Science & Coaching, 2017)
Proper body balance plays a significant role in performing motor skills and it depends upon a number of factors. Its level decreases when the reception of visual stimuli is limited. It may affect the choice of sports activities as well as overall performance. This study sought to assess the levels of selected static balance indices in visually impaired goalball players. Competitors who took part in the goalball tournament of the 2012 London Paralympic Games were included in the study (M=42, F=23). The athletes were divided into groups taking into account tournament level, disability experience, training experience and training loads. Static balance was assessed using AMTI AccuSway stabilographic platform (ACS Model). The study participants performed the following tests: standing on both feet with eyes open and closed (30 s, single left- and right-leg stance with eyes open, single left- and right-leg stance with eyes closed (10 s). The significance of differences between groups in gender, disability experience, tournament level, training loads and starting class was assessed using Mann-Whitney U test. Significant differences were noted between competitors from teams participating in the preliminary and final rounds and between competitors with training experience of up to and above 10 years. Players participating in the final phase presented a higher level of static balance, but those with longer training experience lower than less experienced athletes. No significant differences were observed in the levels of the analysed variables between males and females and within starting classes. The study revealed the significance of static balance in achieving sporting excellence in goalball. ABSTRACT FROM AUTHOR